Determinants of Adolescent Women Early Marriage - Nafisah Anna Hidayati; Suprapti Suprapti; Hening Ryan Aryani; Tarsikah Tarsikah (poltekkes kemenkes mataram, 2023)
Teenage pregnancy can increase the maternal mortality rate (MMR) because the reproductive organs are immature, leading to many birth complications. One of the triggers of teenage pregnancy is early marriage caused by several factors. This study analyzes the determinants of early marriage incidence in adolescent girls. The research sample was 60 respondents in Dau District, Malang Regency. The research method used descriptive quantitative with a total sampling technique. Data were collected with questionnaires distributed door to door and were analyzed using percentages. The results showed that most respondents had junior high school education (63%). In contrast, in the category of early teens, psychological changes occurred at that time, one of which was the period of seeking self-identity. Sociocultural factors in the moderate category (61.7%) affect early marriage, where there is still a hereditary tradition. Economic factors in the moderate category (75%) affect early marriage. There is still an arranged marriage with his brother because the property owned does not fall to someone else. Mass media factors in the moderate category (66.7%) affect early marriage. Pornographic photos and videos seen by chance will upload curiosity to see them. Moreover, the belief factor in the excellent category (71.7%) affects early marriage, and there is a view and belief that adolescent maturity is judged by marital status. Thus, it still relatively high several factors that cause early marriage. Health workers and the government will pay more attention and recognize the pattern of early marriage factors from each region so they can later make the proper regulations or counseling on target.